Implementation of Love-Based Curriculum in the Formation of Islamic Character of Students at Madrasah Tsanawiyah - Abdul Rosyid Teguhdin Hamid (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
This study examines the implementation of a love-based curriculum in the formation of Islamic character of students at Madrasah Tsanawiyah. The phenomenon of moral degradation among adolescents is a serious concern in the world of Islamic education, so a humanistic and rooted in the values of compassion is needed. The purpose of this study is to analyze the implementation of a love-based curriculum, identify teachers' strategies in integrating the value of compassion into learning, and evaluate its impact on the formation of students' Islamic character. This research uses a qualitative approach with a case study design at MTs Negeri 1 Malang City. Data collection was carried out through participant observation, in-depth interviews, and document analysis. The research informants include the head of the madrasah, the deputy head of the curriculum, the subject teacher, and the student. Data analysis used the interactive model Miles, Huberman, and Saldana. The results of the study show that the implementation of a love-based curriculum is carried out through three dimensions: love for Allah, love for others, and love for science. Implementation strategies include an exemplary approach, habituation, and positive reinforcement. The resulting impacts include improving commendable morals, social empathy, and student learning motivation.